2010
DOI: 10.5539/ass.v6n10p133
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates and Online Purchasing Behavior

Abstract: This study examined the attitude towards online purchasing behavior among UPM students. A purposive sampling method was used and the sample comprised of 100 students who studying at Universiti Putra Malaysia (UPM). Data were collected via self-administered questionnaire. The questionnaire consisted of four sections: respondents' socio-demographic background, attitude, purchase perception and website quality. Results indicated that majority of respondents had moderate level of purchase perception and website qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…With regards to the attitudinal aspect, the findings of the present study show that the Internet shoppers are more receptive to both online shopping and online advertising (H8 and H9) than the non-Internet shoppers. These findings are also consistent with those of the recent studies by Brashear et al (2009) andOsman et al (2010). Nevertheless, there are some differences among the Internet shoppers across countries.…”
Section: Resultssupporting
confidence: 95%
“…With regards to the attitudinal aspect, the findings of the present study show that the Internet shoppers are more receptive to both online shopping and online advertising (H8 and H9) than the non-Internet shoppers. These findings are also consistent with those of the recent studies by Brashear et al (2009) andOsman et al (2010). Nevertheless, there are some differences among the Internet shoppers across countries.…”
Section: Resultssupporting
confidence: 95%
“…Factors such as navigation and presentation, convenience, and ease of use lead to trustworthiness (Belanger et al, 2002). The speed of navigation is also important to the success of website design (Osman et al, 2010). Taylor and England (2006) stated that the concept of navigation can include:…”
Section: Website Qualitymentioning
confidence: 99%
“…According to Osman et al (2010), found there is a significant difference in attitude towards online purchasing behaviour by gender and education background. The study concluded that gender, education background, purchase perception and website quality have directly influence on attitude towards online purchasing behavior.…”
Section: Introductionmentioning
confidence: 99%